2014
DOI: 10.1097/coc.0b013e31826b9cf0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes and Role of Chemotherapy in Adults With Newly Diagnosed Medulloblastoma

Abstract: Objective To assess the survival and role of adjuvant chemotherapy in adult medulloblastoma. Methods We reviewed outcomes of 66 patients (aged 18 y or more; median age, 33 y) with medulloblastoma. Forty-four (67%) patients had M0 disease, 9 had M1-M4, and 13 had MX. Thirty-one patients each for whom risk stratification was available were classified as high risk or standard risk. Fifty-six patients had histologic results: classic histology was the most common (n = 46 [84%]), followed by desmoplastic (n = 9), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…We found that PFS and OS were better in patients who had GTR (p=0.020), patients without CSF metastasis (p<0.001), and in the SR group of MB patients (p=0.005). This was also reported in other series (3,7,13,23).…”
Section: █ Conclusionsupporting
confidence: 88%
“…We found that PFS and OS were better in patients who had GTR (p=0.020), patients without CSF metastasis (p<0.001), and in the SR group of MB patients (p=0.005). This was also reported in other series (3,7,13,23).…”
Section: █ Conclusionsupporting
confidence: 88%
“…7,17,18 Call et al demonstrated a nonsignificant trend for improved survival with chemotherapy, but only in adults with high-risk MB (n = 66). 6 The ability to evaluate adjuvant chemotherapy based on the available data is limited by small sample sizes and heterogeneous populations and chemotherapy regimens. Additionally, many patients in these studies did not receive regimens containing cisplatin, an agent that is currently used commonly and is associated with improved disease control in pediatric MB.…”
Section: Neurooncologymentioning
confidence: 99%
“…There are no randomized trials investigating the benefit of chemotherapy in adult MB, and evidence is generally limited to small retrospective series reported over several decades with conflicting results. [6][7][8][9] Furthermore, compared with children, adults may suffer less toxicity from CSI and greater morbidity from chemotherapy. This may lead to hesitancy in using postoperative chemotherapy, …”
mentioning
confidence: 99%
“…This low recruitment was likely due to poorer tolerance of the postradiation chemotherapy and retrospective data supporting that surgery and 36 Gy of craniospinal irradiation with a posterior fossa boost yield a satisfactory 60–70% 5‐year OS . This approach in adults results in overall poorer outcomes and an increased frequency of extraneural metastases compared to children . The need of adjuvant chemotherapy is stressed by findings in a recent large retrospective study, where analogous to children, the addition of chemotherapy to radiation conferred a survival benefit.…”
Section: Epidemiologymentioning
confidence: 99%
“…92 This approach in adults results in overall poorer outcomes and an increased frequency of extraneural metastases compared to children. 93 The need of adjuvant chemotherapy is stressed by findings in a recent large retrospective study, where analogous to children, the addition of chemotherapy to radiation conferred a survival benefit.…”
Section: Medulloblastomamentioning
confidence: 99%